Pelatihan Pembuatan Lilin Aroma Terapi Pada Ibu-Ibu Paguyuban Santa Teresa Calcuta Mipitan Kalurahan Mojo Kecamatan Pasar Kliwon Surakarta - Wiharti, Tri; Hanik, Nur Rokhimah; Nugroho, Anwari Adi; Nur’aini, Citra Aisya; Nurhayati, Suci (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Most of the women who are members of the Santa Teresa Calcuta community work as housewives who need to acquire skills that can increase their family income. They have never received counseling or training on making Aromatherapy Candles from universities or other institutions. From the results of interviews, several residents wanted counseling and training on making aromatherapy candles which could be used as an alternative to therapeutic medicine and could also increase income. For this reason, the Biology Education Study Program Abdimas Team will provide training to the Santa Teresa Calcuta Mipitan Women's Association, Mojo Village, Pasar Kliwon District on making Aromatherapy Candles. They want counseling on this theme because most people don't understand how to make Aromatherapy Candles. The objectives of the community service are; To provide education on how to make Aromatherapy Candles. Training is carried out once. The method used is lecture and question and answer, as well as practical guidance on how to make Aromatherapy Candles. The target of this counseling and training is to increase understanding of how to make Aromatherapy Candles among mothers who are members of the Santa Teresa Calcuta Mipitan Community by 20%. From the results of the training on making Aromatherapy Candles for mothers who are members of the Santa Teresa Calcuta Mipitan Community, Mojo Village, Pasar Kliwon District, Surakarta, it can be concluded that there has been an increase in understanding of the process of making Aromatherapy Lilins from an average score of 41.81 to 81.34, meaning there was an increase in understanding by 39.45 (101.94%). The results of Aromatherapy Candles can be used by mothers as health therapy medicines for their own needs or can also be sold to increase family income.